The Effect of Leverage, Profitability and Sales Growth on Tax Avoidance in Manufacturing Companies Listed on the IDX - Nicky Astria Hutapea; Nurganda Siregar; Christnova Hasugian (CV Edujavare Publishing, 2026)
The purpose of this study was determined and analyze the effect of leverage, profitability, sales growth on tax avoidance in food and beverage sub sector companies listed on The IDX for the 2020 to 2024 period. The study population was 15 sub sector companies listed on The IDX. Observation were 75 samples and were selected using the purposive sampling method. Data is processed using panel data regression statistical test methods. The results of this study prove that leverage not effect on tax avoidance, Profitability and sales growth have a positive effect on tax avoidance on sub sector companies listed on The IDX.